Developmental plasticity and evolutionary explanations. Issue 1 (19th September 2019) - Uller, Tobias; Feiner, Nathalie; Radersma, Reinder; Jackson, Illiam S. C.; Rago, Alfredo
Abstract: Developmental plasticity looks like a promising bridge between ecological and developmental perspectives on evolution. Yet, there is no consensus on whether plasticity is part of the explanation for adaptive evolution or an optional "add‐on" to genes and natural selection. Here, we suggest that these differences in opinion are caused by differences in the simplifying assumptions, and particular idealizations, that enable evolutionary explanation. We outline why idealizations designed to explain evolution through natural selection prevent an understanding of the role of development, and vice versa. We show that representing plasticity as a reaction norm conforms with the idealizations of selective explanations, which can give the false impression that plasticity has no explanatory power for adaptive evolution. Finally, we use examples to illustrate why evolutionary explanations that include developmental plasticity may in fact be more satisfactory than explanations that solely refer to genes and natural selection. Abstract : Can developmental plasticity explain why adaptation happens, or is it always an optional "addߚon" to genes and natural selection? Opinions vary because biologists idealize evolution by natural selection in different ways. Research Highlights: An accessible introduction to the use of idealization in evolutionary biology. Shows why idealizations designed to explain evolution through natural selection prevent an understanding of the role of development, and vice versa. Illustrates why evolutionary explanations that include developmental plasticity can be more satisfactory than explanations that solely refer to genes and natural selection.